Co dalej w dyskusji nad regnum ablatum? : krótki szkic w 30. rocznicę ukazania się artykułu profesora Wacława Korty - Piętkowski, Piotr (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2020)
The article present the contemporary discussion among medievalists on the conflict that occurred at the end of 10th century between Mieszko I, duke of Polans, and Boleslaus II the Pious, the ruler of Bohemia; such conflict has been mentioned by Thietmar, bishop of Merseburg, in his chronicle. The dispute centered on a territory which Thietmar enigmatically referred to as regnum ablatum.
Keywords: regional studies; region; Silesia; Poland; Czech Republic; Germany; regional journal; historical journal